Effect of Massage on Sleep Quality and Motor Development in Infant Aged 3-6 Months - Kusumastuti, Nurry Ayuningtyas; Tamtomo, Didik; Salimo, Harsono (Journal of Maternal and Child Health, 2016)
Background: In theory, infant massage is beneficial for improving sleep quality, gross and fine motor development. Infants aged 3-6 months are able to receive stimulation that may help develop gross and fine motor development. Massage may improve brain function and raise the release of growth hormone, and strengthen muscle. This study aimed to determine of the effect of massage on sleep quality, gross and fine motor development among infant aged 3-6 months.Subject and Method: This was a randomized controlled trial, conducted in Magelang, Central Java, from 1 August to 16 September 2016. A total of 60 infants in Azza Momby Spa, Magelang was selected for this study by simple random sampling. This sample was then allocated at random into massage group (n1=30) and control group (n2=30). The independent variable was infant massage. The dependent variables were sleep quality, gross and fine motor development. The data was collected by using questionnaire. The difference of dependent variables between the two groups were tested by Mann-Whitney.Results: After intervention, infants in the massage group (median=2.00; SD=1.80) slept better than the control group (median=0.00; SD=0.95), and it was statistically significant (p<0.001). Infants in the massage group (median=0.00; SD=0.81) had better gross motor development than the control group (median=0.00; SD=0.72), and it was statistically significant (p=0.043). Infants in the massage group (median=0.00; SD=0.81) had better fine motor development than in the control group (median=0.00; SD=0.48), and it was statistically significant (p=0.018).Conclusion: Massage is effective to improve sleep quality, gross and fine motor development, in infants aged 3-6 months.Keywords: massage, sleep quality, gross and fine motor development, infantCorrespondence:ÃÂ Nurry Ayuningtyas Kusumastuti. Masters Program in Public Health, Sebelas Maret University, Surakarta. Email: nurry0067@yahoo.com.Journal of Maternal and Child Health (2016), 1(3):161-169https://doi.org/10.26911/thejmch.2016.01.03.03